Nasal Delivery of Antigen with the B Subunit of Escherichia coli Heat-Labile Enterotoxin Augments Antigen-Specific T-Cell Clonal Expansion and Differentiation - Apostolaki, Maria (American Society for Microbiology, 2004)
Escherichia coli heat-labile enterotoxin has unique immunogenic and adjuvant properties when administered mucosally to mice. These properties have revealed the potential for its use in the development of mucosal vaccines, an area of increasing interest. However, the inherent toxicity mediated by the A subunit precludes its widespread use. This problem has led to attempts to dissociate toxicity from adjuvant function by use of the B subunit. The ability of the B subunit of E. coli heat-labile enterotoxin (EtxB) to enhance responses against antigens coadministered intranasally is demonstrated here with the use of the DO11.10 adoptive-transfer model, in which ovalbumin (OVA)-specific adoptively transferred T cells can be monitored directly by flow cytometry. Intranasal delivery of OVA with EtxB resulted in increased T-cell proliferative and systemic antibody responses against antigens. The increased Th2 cytokine production detected following in vitro restimulation of splenocyte and cervical lymph node (CLN) cells from the immunized mice correlated with increased OVA-specific immunoglobulin G1 antibody production. Flow cytometric analysis of T cells from mice early after immunization directly revealed the ability of EtxB to support antigen-specific clonal expansion and differentiation. Furthermore, while responses were first detected in the CLNs, they rapidly progressed to the spleen, where they were further sustained. Examination of CD69 expression on dividing cells supported the notion that activation induced by the presence of antigens is not sufficient to drive T-cell differentiation. Furthermore, a lack of CD25 expression on dividing cells suggested that EtxB-mediated T-cell clonal expansion may occur without a sustained requirement for interleukin 2.